Impactos da pandemia da covid-19 na produção de resíduos sólidos urbanos durante o período de veraneio no litoral norte do estado do Rio Grande do Sul - Brasil - Cristovão, Roger da Silva (Universidade do Vale do Rio dos Sinos, 2021)
The COVID-19 pandemic caused diverse impacts of global proportions. An increase in the production of urban solid waste was noted in many countries, including Brazil, due to the increase in population and the lack of public control policies. This present work aims to verify if there was an increase in the production of urban solid waste during the pandemic period in the North Coast of the State of Rio Grande do Sul, during the summer season, when many people went to the beaches to escape their routine or even isolate themselves , avoiding contact with people infected with the SARS-CoV-2 virus. The results were obtained by collecting data on the production of waste in the municipalities, together with the municipalities and municipal secretariats involved. Statistical tests were applied where it was proven that of the eight cities that make up the north coast of the state of Rio Grande do Sul (Arroio do Sal, Balneário Pinhal, Capão da Canoa, Cidreira, Imbé, Torres, Tramandaí and Xangri-Lá), only two contained statistically significant data. With this study, it was possible to verify the impacts caused by garbage, while we verified the impacts caused by COVID-19 in the studied municipalities, verifying some sectors that started to produce more waste in this period, as well as the impacts that garbage causes in our environment. There is a clear need for environmental policies to better manage urban solid waste, as well as to assess the impacts they cause on the North Coast of Rio Grande do Sul.
Keywords: Lixo; Coronavírus; Praia; Costa; Fauna; Turistas; Orla; Trash; Coronavirus; Beach; Coast; Tourists; Edge